General practitioners' views of pharmacists' current and potential contributions to medication review and prescribing in New Zealand - Hatah E; Braund R; Duffull SB; Tordoff J (CSIRO Publishing, 2013)
INTRODUCTION: Internationally, non-medical practitioners are increasingly involved in tasks traditionally undertaken by general practitioners (GPs), such as medication review and prescribing. This study aims to evaluate GPs' perceptions of pharmacists' contributions to those services. METHODS: Semi-structured interviews were carried out in two localities with GPs whose patients had and had not undergone a pharmacist-led adherence support Medication Use Review (MUR). GPs were asked their opinions of pharmacists' provision of MUR, clinical medication review and prescribing. Data were analysed thematically using NVivo 8 and grouped by strengths, weaknesses, opportunities and threats (SWOT) category. FINDINGS: Eighteen GPs were interviewed. GPs mentioned their own skills, training and knowledge of clinical conditions. These were considered GPs' major strengths. GPs' perceived weaknesses were their time constraints and heavy workloads. GPs thought pharmacists' strengths were their knowledge of pharmacology and having more time for in-depth medication review than GPs. Nevertheless, GPs felt pharmacist-led medication reviews might confuse patients, and increase GP workloads. GPs were concerned that pharmacist prescribing might include pharmacists making a diagnosis. This is not the proposed model for New Zealand. In general, GPs were more accepting of pharmacists providing medication reviews than of pharmacist prescribing, unless appropriate controls, close collaboration and co-location of services took place. CONCLUSION: GPs perceived their own skills were well suited to reviewing medication and prescribing, but thought pharmacists might also have strengths and skills in these areas. In future, GPs thought that working together with pharmacists in these services might be possible in a collaborative setting.